Government Strategy in Handling the Siabu Air Weapon Range (AWR) Conflict in Kampar Regency, Riau Province to Support National Security: Strategi Pemerintah dalam Menangani Konflik di Lapangan Tembak Udara (AWR) Siabu di Kabupaten Kampar, Provinsi Riau untuk Mendukung Keamanan Nasional - Restu Putri Pamungkas; Asep Adang Supriyadi; Syamsunnasir Syamsunnasir; Bambang Kustiawan; Siham El-Kafafi (Indonesian Journal of Counter Terrorism and National Security, 2025)
This study discusses the dynamics of conflict related to the Siabu Air Weapon Range (AWR) in Kampar Regency, Riau Province, involving the Indonesian Air Force's Roesmin Nurjadin Air Base and the communities surrounding the area. The conflict arose due to the use of the AWR land as an Indonesian Air Force shooting range, which borders directly on palm oil plantations owned by the community, thus posing a potential threat to national security. The purpose of this study is to analyze the role and strategies of the Kampar Regency Government in resolving the dispute over the use of the Siabu AWR land as part of efforts to support national security. The research used a qualitative approach through interviews, field observations, and document reviews. The findings show that stronger involvement from the local government is needed through the formulation of regional regulations governing the Siabu AWR training area, strengthening interagency coordination through an Interagency Working Group, and establishing vertical institutions in the region to support defense outreach activities. This study recommends the implementation of an Interagency Working Group-based National Security Strategy to produce more proportional and effective policy synergies between institutions, utilizing a customary-based approach to strengthen national security in a sustainable manner.